2019
DOI: 10.15381/anales.803.16515
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas y mortalidad intrahospitalaria en pacientes con insuficiencia renal aguda en hemodiálisis, en el Hospital Nacional Guillermo Almenara Irigoyen, EsSalud, 2014-2015

Abstract: Introducción: No existen datos oficiales sobre los pacientes con insuficiencia renal aguda (IRA) en el Perú. La mayor parte de la información proviene de centros aislados en otros países. Objetivo: Describir las características clínicas y la mortalidad intrahospitalaria en pacientes con insuficiencia renal aguda, en hemodiálisis, atendidos en un hospital de tercer nivel del Perú. Método: Estudio transversal, realizado en pacientes con diagnóstico de IRA en hemodiálisis, atendidos en el Hospital Guillermo Almen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Those characteristics include older age, the presence of multiple comorbidities, sepsis as the cause of AKI, and the need for care in intensive care units. [8][9][10] However, it is necessary to point out that these studies used medical records or the International Classification of Diseases (ICD-10) coding to identify patients with AKI, so it is not known which criteria were used to establish the diagnosis. [8][9][10] A study on the basis of the registry of AKI cases reported by MINSA between 2005 and 2016 and the data reported from death certificates during the same period showed that AKI cases increased and AKI-related deaths decreased over time.…”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%
See 4 more Smart Citations
“…Those characteristics include older age, the presence of multiple comorbidities, sepsis as the cause of AKI, and the need for care in intensive care units. [8][9][10] However, it is necessary to point out that these studies used medical records or the International Classification of Diseases (ICD-10) coding to identify patients with AKI, so it is not known which criteria were used to establish the diagnosis. [8][9][10] A study on the basis of the registry of AKI cases reported by MINSA between 2005 and 2016 and the data reported from death certificates during the same period showed that AKI cases increased and AKI-related deaths decreased over time.…”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%
“…[8][9][10] However, it is necessary to point out that these studies used medical records or the International Classification of Diseases (ICD-10) coding to identify patients with AKI, so it is not known which criteria were used to establish the diagnosis. [8][9][10] A study on the basis of the registry of AKI cases reported by MINSA between 2005 and 2016 and the data reported from death certificates during the same period showed that AKI cases increased and AKI-related deaths decreased over time. 7 The agestandardized AKI incidence rate, regardless of severity, increased from 9.6 per 100,000 in 2005 to 14.0 per 100,000 in 2016, and the age-standardized mortality rate decreased from 2.3 per 100,000 in 2005 to 1.2 per 100,000 in 2016 7 (Figure 1).…”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%
See 3 more Smart Citations